Scales of Analysis: the Usage of Appropriate Magnification in Use-Wear Studies - Bradfield, J. (Археологія, 2022)
The interpretative potential of microscopic use-wear polishes is a factor of the scale of analysis. Observational surface area decreases in inverse proportion to magnification. In this paper I present the results of polishes on bone tools that have developed from fricative contact with nine different materials. Microwear polish is viewed at five different magnifications. I show that 50x―200x magnification, or observational areas of 0.4―2.0 mm², is the most appropriate scale of analysis of use-wear polishes regardless of whether one is conducting morphological identifications or relying on surface texture analysis software. The images presented here are meant to serve as an online reference collection to allow use-wear analysts to visualise how polish appearances change at different levels of magnification.